ARTICLE REVIEW DETEKSI DINI AMBLIOPIA - Nabila Yoli Rahmadani; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Amblyopia is a developmental disorder of vision. It is caused by failure of visual cortical development in one or both eyes due to congenital abnormalities early in life. Amblyopia occurs early in life when the developing visual system fails to transmit sharp images to the visual cortex. It can be caused by media opacities, cataracts, strabismus, or an anisometropic refractive error that places one eye at a developmental disadvantage in the other. Amblyopia is the leading cause of monocular vision loss in children, with an estimated prevalence of 1% to 6% and is responsible for permanent vision loss in 2.9% of adults. In general, amblyopia does not cause symptoms, so it is very important to perform visual function screening to detect the risk of developing amblyopia. Accurate screening methods that pediatricians, family care practitioners, nurses, or community organizations can use can identify amblyopia at a time when treatment is most effective, so amblyopia can be treated more effectively when detected early. This paper uses the article review method using sources such as journals and books. The purpose of this writing is to find out the steps for early detection of amblyopia. The results of this paper found that early detection can be done by visual screening consisting of risk history factors and visual acuity abnormalities (preferential search techniques (Teller acuity cards, Cardiff acuity tests), fixation preference tests or image charts (Kay charts and Lea symbols). and Photoscreening) in children aged 3-5 years. The conclusion obtained is that early amblyopia screening can help with treatment and a better prognosis.